Historical background and constraints of a grapevine germplasm foundation in Hajdú-Bihar county, Eastern Hungary - Rakonczás, N. (International Journal of Horticultural Science, 2018)
The historical background of Debrecen linked to viticulture and wine-making stands mainly on the lack of drinkable water, the necessity of drinkable liquid during wartime and epidemics. The special character of the city evolved together with the changing lives of citizens and the increasing trade importance of the city. Period of Turkish occupation gave impetus to the formation of the 11 vine gardens of the settlement. After the devastation of rootmite and peronospora ‘Kadarica’ and ‘Nagy burgundy’ (‘Blaufrankish’), in smaller proportion - on lower sites – ‘Cabernet’ were planted. As white varieties ‘Ezerjó’, ‘Olasz Rizling’, ‘Kövidinka’, ‘white Mustos’, in smaller proportion ‘Szlankamenka’, ‘Erdei’, ‘Szilvaner’, ‘Mézesfehér’, ‘Bakar’, ‘Veltelini’ (red), ‘Fehér burgundi’ (? white burdunder), ‘Rajnai rizling’, ‘Red Tramini’, ‘Furmint’, ‘Muscat Lunel’, ‘Járdovány’ and ‘Juh-fark’ were planted. After the Trianon treaty in 1920, 2/3rd of Hungary was cut away. Érmellék wine region was also cut in two, thus Debrecen broke away from its wine region. Legal regulations after the World War II. (1959) referred back to variety application advised in 1924 for “place suitable for good wine production, not included in any wine region”, like Debrecen listing ’Ezerjó’, ’Mézesfehér’, ’Olaszrizling’, ’Bánáti rizling’, ’Furmint’, ’Hárslevelű’, ’Kövidinka’, Kecskemét virága’, ’Piros szlankamenka’,’Pozsonyi fehér’; ’Kadarka’, ’Oportó’ and ’Kékfrankos’ (Blaufrankish). The political changes of 1990 and Hungary’s admission to the Eurepoean Union almost annihilated the wine production of Debrecen. However little gardens conserved historic varieties which could date back even to many centuries. Through a local magazine a collecting work was announced pointing to gather ancient local (Vitis vinifera conv. pontica) varieties forming a genebank, established on the experimental station of the University of Debrecen. In 2014, about 112 items were collected (accessions). As a 2nd round of the work, with a more detailed and precise work, further 81 items were put into the reservatum. The latter represent single stuck collection, whereas the first ones are to be studied az mixed items. Most notable accession names (ACENAME) of the work are: ‘Fehér gohér’, ‘Veres gohér’, ‘Fekete gohér’, ‘Kék gohér’, ‘Erdei’, ‘Ezerjó’, ‘Kűbeli’, ‘Rizling’, ‘Mézes fehér’, ‘Dinka’, ‘Madling’, ‘Bakator’ and ‘Kadarka’. Simulteneously with the strenghening and morphological description of conserved stucks genetic identification of the items is being elaborated. Database comprising FAO/IPGRI multi-crop passport descriptors and OIV Primary descriptor priority list are to be published on-line in between the development of the platform.